2016
DOI: 10.3390/ijms17081230
|View full text |Cite
|
Sign up to set email alerts
|

Is Upregulation of Aquaporin 4-M1 Isoform Responsible for the Loss of Typical Orthogonal Arrays of Particles in Astrocytomas?

Abstract: The astrocytic endfoot membranes of the healthy blood-brain barrier—contacting the capillary—are covered with a large number of the water channel aquaporin 4 (AQP4). They form orthogonal arrays of particles (OAPs), which consist of AQP4 isoform M1 and M23. Under pathologic conditions, AQP4 is distributed over the whole cell and no or only small OAPs are found. From cell culture experiments, it is known that cells transfected only with AQP4-M1 do not form OAPs or only small ones. We hypothesized that in astrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…The role of AQP4 isoforms in glioblastoma biology has been addressed in earlier studies, which have shown that high-grade gliomas display higher expression of AQP4 than low-grade tumors (7). Furthermore, OAPs have been shown to be disintegrated or absent in glioblastomas, and more recently an inverse correlation between OAP prevalence and malignancy was demonstrated (8).…”
Section: Mahmood Amiry-moghaddammentioning
confidence: 99%
“…The role of AQP4 isoforms in glioblastoma biology has been addressed in earlier studies, which have shown that high-grade gliomas display higher expression of AQP4 than low-grade tumors (7). Furthermore, OAPs have been shown to be disintegrated or absent in glioblastomas, and more recently an inverse correlation between OAP prevalence and malignancy was demonstrated (8).…”
Section: Mahmood Amiry-moghaddammentioning
confidence: 99%
“…An interesting study by Noell and colleagues reports none or only small OAPs on glioblastoma samples analyzed by freeze-fracture electron microscopy, indicating that redistribution of AQP4 and OAPs could be one of the earliest indicators of glioma transformation (17). Interestingly, although a correlation between the decrease in OAPs and increasing grade of malignancy of astrocytomas has been reported, this was not consistent with an upregulation of M1-AQP4 in relation to M23-AQP4 (18).…”
Section: Introductionmentioning
confidence: 96%
“…Interestingly, the abundance and the size of OAPs differ not only in comparison with healthy cells but also between different stages of glioblastomas. High-grade astrocytoma tumors are reported to express only a few typical OAPs, whereas low-grade astrocytomas express more OAPs; this discovery is among the important steps in unraveling of the role of OAPs in astrocytoma malignancy [52,74]. Functional rearrangements of OAPs in glioblastomas remain to be further evaluated from the perspective of rearrangements of different AQP4 isoforms, because not all AQP4 molecules in the plasma membranes of glioblastoma cells are arranged in OAPs [52,71].…”
Section: Oaps and Glioma Invasivenessmentioning
confidence: 93%
“…The expression of AQP4c (M23) directed glioma cells to apoptosis through interactions mediated by actin cytoskeleton, therefore reducing the invasive potential [69]. The protein expression of AQP4 in human glioblastoma is indeed upregulated in comparison with healthy brain tissue [52,74,75]. However, the ratio of expression between AQP4a (M1) and AQP4c (M23) appears to remain similar [52]; therefore, one has to look at additional levels that affect the incorporation of AQP4 into the plasma membrane and their interactions within OAPs.…”
Section: Oaps and Glioma Invasivenessmentioning
confidence: 99%